2022
DOI: 10.1021/acs.est.2c01834
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antibiotic Resistome in Hospital Wastewater during the COVID-19 Pandemic: Is the Initial Phase of the Pandemic Contributing to Antimicrobial Resistance?

Abstract: Since the COVID-19 pandemic started, there has been much speculation about how COVID-19 and antimicrobial resistance may be interconnected. In this study, untreated wastewater was sampled from Hospital A designated to treat COVID-19 patients during the first wave of the COVID-19 pandemic alongside Hospital B that did not receive any COVID-19 patients. Metagenomics was used to determine the relative abundance and mobile potential of antibiotic resistant genes (ARGs), prior to determining the correlation of ARGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…Note that a significant negative correlation was also observed between the sul 1 gene, conferring resistance to sulfonamides, quantified through qPCR and the COVID-19 cases (See Section ). Similar results were observed in a study of hospital wastewater, where a negative correlation was reported between ARGs belonging to drug classes aminoglycoside, peptides, beta-lactam, fluoroquinolone, and lincosamide and the number of COVID-19 patients . This negative correlation could be attributed to a variety of reasons, including high rates of antibiotic prescription in the initial months of the pandemic followed by the decrease in overall antibiotic usage as the pandemic progressed .…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Note that a significant negative correlation was also observed between the sul 1 gene, conferring resistance to sulfonamides, quantified through qPCR and the COVID-19 cases (See Section ). Similar results were observed in a study of hospital wastewater, where a negative correlation was reported between ARGs belonging to drug classes aminoglycoside, peptides, beta-lactam, fluoroquinolone, and lincosamide and the number of COVID-19 patients . This negative correlation could be attributed to a variety of reasons, including high rates of antibiotic prescription in the initial months of the pandemic followed by the decrease in overall antibiotic usage as the pandemic progressed .…”
Section: Resultssupporting
confidence: 85%
“…Similar results were observed in a study of hospital wastewater, where a negative correlation was reported between ARGs belonging to drug classes aminoglycoside, peptides, beta-lactam, fluoroquinolone, and lincosamide and the number of COVID-19 patients. 32 This negative correlation could be attributed to a variety of reasons, including high rates of antibiotic prescription in the initial months of the pandemic followed by the decrease in overall antibiotic usage as the pandemic progressed. 12 Interestingly, the correlation was not significant for either aminoglycoside or sulfonamide when prepandemic samples were included (COVID-19 cases for prepandemic samples were considered zero), underscoring the need for inclusion of samples from a longer time period to understand any pandemic-related changes.…”
Section: Metagenomic Insights Into Arg Abundancementioning
confidence: 99%
See 2 more Smart Citations
“…The ongoing global pandemic of coronavirus disease 2019 (COVID-19) poses a serious threat to public health ( Huang et al, 2020 , Platto et al, 2020 ). Long before the COVID-19 epidemic, antibiotic resistance was a global public health concern, and it remains so ( Wang et al, 2022 ). Particularly, various antibiotics were used in pandemic disease treatments ( Miranda et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%